High Calcification Costs Limit Mussel Growth at Low Salinity - Sanders, Trystan; Schmittmann, Lara; Nascimento-Schulze, Jennifer C.; Melzner, Frank (Frontiers in Marine Science, 2018)
In coastal temperate regions such as the Baltic Sea, calcifying bivalves dominate benthic communities playing a vital ecological role in maintaining biodiversity and nutrient recycling. At low salinities, bivalves exhibit reduced growth and calcification rates which is thought to result from physiological constraints associated with osmotic stress. Calcification demands a considerable amount of energy in calcifying molluscs and estuarine habitats provide sub-optimal conditions for calcification due to low concentrations of calcification substrate and large variations in carbonate chemistry. Therefore, we hypothesise that slow growth rates in estuarine bivalves result from increased costs of calcification, rather than costs associated with osmotic stress. To investigate this, we estimated the cost of calcification for the first time in benthic bivalve life stages and the relative energy allocation to calcification in three Mytilus populations along the Baltic salinity gradient. Our results indicate that calcification rates are significantly reduced only in 6 psu populations compared to 11 and 16 psu populations, coinciding with ca. 2 – 3-fold higher calcification costs at low salinity and temperature. This suggests that reduced growth of Baltic Mytilus at low salinities results from increased calcification costs rather than osmotic stress related costs. We also reveal that shell growth (both calcification and shell organic production) demands 31 – 60 % of available assimilated energy from food, which is significantly higher than previous estimates. Energetically expensive calcification represents a major constraint on growth of mytilids in the estuarine and coastal seas where warming, acidification and desalination are predicted over the next century.